2020
DOI: 10.1111/aswp.12205
|View full text |Cite
|
Sign up to set email alerts
|

Trust and well‐being: Evidence from Indonesia

Abstract: Over the past three decades, the benefits of trust have been the subject of interest in many academic and scientific fields. Economists found that trust enhances economic performance in a country by facilitating transactions and investments, by reducing unnecessary costs, and by enhancing the quality of economic policies (Knack, 2001). Some researchers have estimated that trust has an income equivalent value (Helliwell & Wang, 2011). Psychologists and social scientists found that trust facilitates connections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
5
8
0
Order By: Relevance
“…This corroborates prior studies that found positive effects of education on subjective well-being (Kuroki, 2011). As expected, self-rated health was an important predictor of both happiness and life satisfaction, which corroborate the findings of previous studies (Nizeyumukiza et al, 2020). Extroverted people were more satisfied with life and happier than their counterparts.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This corroborates prior studies that found positive effects of education on subjective well-being (Kuroki, 2011). As expected, self-rated health was an important predictor of both happiness and life satisfaction, which corroborate the findings of previous studies (Nizeyumukiza et al, 2020). Extroverted people were more satisfied with life and happier than their counterparts.…”
Section: Resultssupporting
confidence: 91%
“…The literature has shown that gender (Graham & Chattopadhyay, 2013;Nopiyanto, Raibowo, & Prabowo, 2021), marital status (Cao, Krause, Saunders, & Clark, 2015), education (Mrva, 2020) religiosity (Dilmaghani, 2017), personality (Lucas, 2018), social trust (Nizeyumukiza, Cilik Pierewan, Ndayambaje, & Ayriza, 2020), and health (Ndayambaje, Pierewan, Nizeyumukiza, Nkundimana, & Ayriza, 2020) are all related to subjective well-being. Therefore, these variables are susceptible to confound the relationship between physical activity and subjective well-being and will be controlled in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Those who completed senior high school and high education were more satisfied with life than those who completed only primary education. This is in line with previous studies which found happiness to be more associated with having completed senior high school and high education than having completed elementary school in Indonesia (Nizeyumukiza et al, 2020). Social trust was significantly associated with life satisfaction which corroborates previous findings from Indonesia (Nizeyumukiza et al, 2020;Pierewan & Veenhoven, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…A report of the Gallup showed that 94% of people in the Unites States reported that they believed in God, 82% claimed that religion was important to them (Gallup, 2009). In Indonesia, a study used a community survey and reported that more than 72% reported that they were religious (Nizeyumukiza, Cilik Pierewan, Ndayambaje, & Ayriza, 2020). Given this prevalence of perceived religiosity in people's life world widely, it is assumable that it plays an important role in how people conceptualize their life.…”
Section: Introductionmentioning
confidence: 99%
“…This means that trustfully people experience high level of being satisfied with life compared to those who are neutral or those who do not. Another study from Indonesia found similar results (Nizeyumukiza, Cilik Pierewan, Ndayambaje, & Ayriza, 2020). In addition, this study found that religiosity has a positive correlation with satisfaction with life.…”
Section: Resultssupporting
confidence: 75%